Incongruency in Discourse: A Violation of the "Cooperative Principle"? - Okolo, Bertram (Meta, 1996)
AbstractIncongruency, when regarded as a verbal behavioral act that functions to create contradictory meanings in discourse, seems to violate aspects of the Gricean "Cooperative Principle" that are supposed to guide our every-day conversational encounters. With the aid of actual examples, this paper looks at incongruent conversational exchanges and discusses the factors governing their toleration in conversational interaction, the cross-cultural aspects of incongruent behavioral acts, their translational implications, and suggests that strict observances of the "Cooperative Principle" are restricted to particular types of discourses.